Marine aquaculture in Turkey and potential finfish species - Deniz H. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
The first marine aquaculture commercial ventures in Turkey were set up in 1985. Since then production has grown rapidly, from 35 tons in 1986 to 18,000 tons in 1997. Sea bream is first marine cultured species and sea bass, shrimp, salmon, sea trout have followed it. A number of other secondary native species that could be considered for marine aquaculture are: groupers, Black Sea turbot, eels, oysters, sharpnosed sea bream, common sea bream, Black Sea sea trout, lobster, sturgeon and sole. There are also exotic spcies under consideration, e.g. Atlantic turbot, Indian redtailed shrimp, rabbitfish, Japanese sea bream and landlocked salmon. In addition, a joint project on Black Sea turbot with Japan International Cooperation Agency (JICA) is undertaken on the Black Sea coast. The first results has been obtained fingerlings of turbot which is about 8000 are being reared. Studies on growing, feeding and broodstocks management are continuing.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)